Przegląd teorii aprobaty społecznej - Izdebski, Paweł; Żbikowska, Karolina; Kotyśko, Martyna (Acta Universitatis Lodziensis. Folia Psychologica, 2013)
The aim of this review is to present the most important theories of social approval. There are one-factor and two-factor theories of social approval distinguished. The most important among one-factor theories are: Edwards and Crowne–Marlowe models of social approval, and among two-factor theories are: Wiggins, Damarin and Messick, Sackeim and Gur, and Paulhus. There are also presented questionnaires based on theories mentioned above, which are used to measure the need of social approval: the Edwards Social Desirability Scale, the Marlowe–Crowne Social Desirability Scale, the Self-Deception Questionnaire and the Other-Deception Questionnaire created by Sackeim and Gur, and the Balanced Inventory of Desirable Responding (BIDR) designed by Paulhus, which consists of two subscales: Self-Deceptive Enhancement and Impression Management.